Micronized fibres affect in vitro fermentation under normal buffered and osmotic stress conditions using porcine inocula. Issue 6 (28th January 2015) - Aumiller, T.; Mosenthin, R.; Rink, F.; Hartung, K.; Weiss, E.
Summary: In this in vitro study, the modified Hohenheim gas test was used to determine fermentation activity and bacterial composition of pig's faecal microbial inoculum, when fermenting a standard pig diet with varying levels of crude protein (CP; 20, 24 and 28% CP), and supplemented with one of three fibre sources manufactured by micronization treatment. These were wheat envelopes (MWE), pea fibre (MPF) and lupine fibre (MLF). For comparison, inulin was used. As intestinal bacteria have to cope with varying osmotic conditions in their ecosystem, fermentation was performed under normal buffered and osmotic stress conditions. After 24 h of fermentation, total gas production and ammonia production were measured. In addition, the effect of MWE and inulin on short‐chain fatty acid (SCFA) production and numbers of total eubacteria, Lactobacillus spp., Bifidobacterium spp., Enterobacteriaceae, Enterococcus spp., Clostridium cluster XIVa and Clostridium cluster IV, were determined using quantitative real‐time PCR. Under normal buffered conditions, supplementation of MWE resulted in increased (p < 0.05) SCFA, acetic, propionic and valerianic acid production at CP levels of 20 and 28%. There was an increase (p < 0.05) in ammonia production for the micronized supplements, and for MWE an increased (p < 0.05) branched‐chain proportion was observed, possibly due to higher availability of protein for fermentation which was released during the micronization process. Osmotic stress conditions reduced (p < 0.05) total gas as well as total SCFA, acetic and propionic acid production for all treatments, while cell counts were increased (p < 0.05) for Bifidobacterium spp., Enterococcus spp. and Lactobacillus spp. Under normal buffered conditions in combination with 24 and 28% CP levels, lactobacilli were increased for MWE, compared to inulin (p < 0.05). In conclusion, micronized supplements such as MWE may beneficially modulate pigs' intestinal microbiota by increasing SCFA production in addition to a selective proliferation of lactobacilli.